PENGARUH SIKAP, NORMA SUBJEKTIF, KONTROL PERILAKU PERSEPSI TERHADAP MINAT PERILAKU PENGGUNAAN SISTEM INFORMASI AKUNTANSI BERBASIS E-COMMERCE : (Studi Kasus Pada Mahasiswa Prodi Akuntansi Universitas Flores Ende) - Hasan, Nur’Syabannia; Marselina , Apriana; Ismail, Nuraini (Jurnal Riset Ilmu Akuntansi, 2020)
This study purposes to examine the factors that influence intention of behaviour on the use e-commerce based accounting information system. This research was conducted at Flores University in Ende with a population of 576 accounting students. Sample used in this research are 85 respondent. This research uses a quantitative approach. Data was collected using observation, interview, and questionnaire. This study used several tests including instrument test, classical assumption test, and hypotheses test. The result of study shows that (1) attitude usefulness have effect to use behaviour intention of e-commerce based accounting informstion system. (2) subjective norm usefulness have effect to use behaviour intention of e-commerce based accounting informstion system. (3) perceived behaviot control usefulness have effect to use behaviour intention of e-commerce based accounting information system.